2008
DOI: 10.1086/525039
|View full text |Cite
|
Sign up to set email alerts
|

A Fisk‐Parker Hybrid Heliospheric Magnetic Field with a Solar‐Cycle Dependence

Abstract: We present a refinement of the Fisk-Parker hybrid field of Burger and Hitge which now includes a region bordering the solar rotational equator where magnetic field footpoint motion occurs only through diffusive reconnection. The hybrid field, therefore, only occurs above a certain latitude in a given hemisphere, and in the equatorial region the field is a pure Parker field. We also propose a simple qualitative model for the solar cycle dependence of the hybrid field, taking into account changes in the tilt ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
140
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(144 citation statements)
references
References 52 publications
4
140
0
Order By: Relevance
“…thus consisting of one component directed along the mean HMF, κ || is taken from Burger et al (2008), and two component perpendicular to it, κ ⊥r/θ is taken from Burger et al (2000). As input for κ || various turbulence quantities are needed, most notable the HMF variance δB 2 .…”
Section: The Modulation Modelmentioning
confidence: 99%
“…thus consisting of one component directed along the mean HMF, κ || is taken from Burger et al (2008), and two component perpendicular to it, κ ⊥r/θ is taken from Burger et al (2000). As input for κ || various turbulence quantities are needed, most notable the HMF variance δB 2 .…”
Section: The Modulation Modelmentioning
confidence: 99%
“…To this end, we present here results for the rigidity and spatial dependences of the proton parallel and perpendicular mean-free paths using outputs yielded by the new, generalized, self-consistent two-component turbulence transport model discussed above. The parallel mean-free path used here is that employed by, e.g., Burger et al (2008), and derives from quasilinear theory (QLT). We present a novel expression for the proton perpendicular mean-free path, derived from the random ballistic decorrelation (RBD) interpretation of the nonlinear guiding center (NLGC) theory of Matthaeus et al (2003) as presented by Ruffolo et al (2012).…”
Section: Relevance For Cosmic-ray Transport Coefficientsmentioning
confidence: 99%
“…Alania et al (2008) studied the phase distribution of the 27-day variation in SW speed and found more stable and long-lived heliolongitudinal structures during A > 0 minima, possibly affecting the amplitude of 27-day variation of GCR intensity and causing the observed Hale cycle dependence. Burger et al (2008) used a Fisk-type hybrid field in modeling the GCR intensity variation and also found a larger 27-day variation during positive-polarity minima.…”
Section: Introductionmentioning
confidence: 99%